Barriers to Implementation of EvidenceBased Nursing Care from the Perspective of Nursing Instructors of Nursing and Midwifery Faculty of Rafsanjan and Kerman Iran - Lida Soltani; Fariba Mazhari; Esmat Nouhi; Sekineh Sabzevari (Kerman University of Medical Sciences, 2017)
Background & Objective: Evidencebased care is using evidence obtained from research into clinical practice based on the patients condition and type of illness This study aimed to investigate the barriers to implementation of evidencebased nursing care based on instructors and educators opinion Methods: This was a crosssectional study that was performed with the participation of 70 faculty members and nonfaculty members of School of Nursing of Rafsanjan and Kerman Iran with different educational levels Inclusion criteria were having at least bachelors degree and twoyears work experience Data was analyzed using SPSS and descriptive statistics (frequency and percentage) Results: Women and men instructors comprised 686% and 314% of respondents respectively Most of them (443%) were 35 to 44 years of age In their opinion the major obstacles to implementation of evidencebased nursing in the education domain was lack trained staff to use the findings from research in evidencebased care with 943% In the management domain lack of knowledge of nursing managers regarding the importance of evidencebased nursing care with 857% and in the individual domain lack of adequate skills for the implementation of evidencebased practice and lack of nurses knowledge of evidencebased practice with 857% were also mentioned by participants as obstacles Conclusion: The main barriers in the application of evidencebased nursing can be noted in the domains of education and management Therefore a big step forward in this regard will be providing access to the resources and facilities library and continuing education for nursing staff and updating their information in the field of evidencebased care which requires cooperation of the managers at different levels of planning